Factors Impacting Students’ Decision to Enroll in UII’S Doctoral Program in Islamic Law: An Analysis - Qotadah, Hudzaifah Achmad; Mu'allim, Amir; Budiwati, Anisah; Yusdani, Yusdani; Ahmad, Muchsin; Arfaizar, Januariansyah (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2023)
This research aims to determine students' preferences when pursuing a doctorate in Islamic law studies at the Indonesian Islamic University (UII). The participants in this research were Islamic law students enrolled in the doctoral program (HI-PD) at the Indonesian Islamic University in Yogyakarta between 2019 and 2022. Interviews were used to gather information in this qualitative study, and 39 students from HI-PD UII participated as research informants. According to the research findings, students' preferences in selecting the HI-PD study program can be categorized according to a number of different factors, including costs, facilities, human resources, reference groups, and recommendations.